1997
DOI: 10.1007/s002130050410
|View full text |Cite
|
Sign up to set email alerts
|

Central 5-HT depletion enhances impulsive responding without affecting the accuracy of attentional performance: interactions with dopaminergic mechanisms

Abstract: A series of ten experiments examined the effects of profound central 5-HT depletion on attentional performance in the rat in the five-choice serial reaction time task, and also determined the effects of such depletion on responding affected by d-amphetamine and by selective dopamine receptor antagonists. Rats were trained to detect and locate brief visual stimuli randomly presented in one of five spatial locations. When performance had stabilised (> 80% correct, < 20% omissions), selective central 5-HT depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
332
6
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(379 citation statements)
references
References 36 publications
40
332
6
1
Order By: Relevance
“…Conceivably the possibility of obtaining a reduction was limited by a 'floor effect'. A further study showed a tendency to reduced premature responses after the dopamine D2 antagonist, sulpiride, and a significant reduction after the dopamine D1 antagonist SCH23390 (Harrison et al, 1997). It is possible that both a reduction in the secondary-reinforcing properties of the stimulus alcoves and some motor disturbance contribute to these effects of haloperidol.…”
Section: Discussionmentioning
confidence: 92%
“…Conceivably the possibility of obtaining a reduction was limited by a 'floor effect'. A further study showed a tendency to reduced premature responses after the dopamine D2 antagonist, sulpiride, and a significant reduction after the dopamine D1 antagonist SCH23390 (Harrison et al, 1997). It is possible that both a reduction in the secondary-reinforcing properties of the stimulus alcoves and some motor disturbance contribute to these effects of haloperidol.…”
Section: Discussionmentioning
confidence: 92%
“…Other human and animal studies DA modulates responses to positive/negative rewards, salient events and arousal-producing stimuli (Everitt et al, 2000;Liberzon et al, 2003;Horvitz, 2000) CSF HVA levels are related to impulsivity in BPD (Coccaro, 1998;Chotai et al, 1998); to self-injurious and violent behavior (Winchel and Stanley, 1991;Soderstrom et al, 2001) DA receptor activity in the DLPFC modulates working memory and cognition (Arnsten et al, 1994;Goldman-Rakic, 1996;Arnsten and Goldman-Rakic, 1998) DA modulates emotional responses mediated by the amygdala-VTA-PFC circuits (Horvitz, 2000) DA dysfunction is involved in drug addiction (Modell et al, 1993;Volkow and Fowler, 2000) PCP-induced cognitive impairment correlates with DA levels in the DLPFC (Jentsch et al, 1997) Stress alters DA activity in the amydala and PFC (Finlay and Zigmond, 1997;Doherty and Gratton, 1999) DA mediates aggression and attack in rats (Wade et al, 2000;Vukhac et al, 2001) DA modulates cognitive processes at NMDA receptors (Williams and Goldman-Rakic, 1995) DA modulates conditioned fear responses (Guarraci et al, 1999) DA stimulates impulsive behavior in rats (Harrison et al, 1997) D1 agonist dilhydrexidine enhances cognitive performance and stimulates Ach release in the PFC (Steele et al, 1997;Schneider et al, 1994) Microdialysates of the PFC and the NAC suggest DA dysfunction is a risk factor for impulsivity (Van Erp and Miczek, 2000;Dalley et al, 2002) DA dysfunction in the DLPFC is related to cognitive impairment in SCZ, SPD, and normal subjects (Goldberg et al, 2003;Siever et al, 2002) DAFdopamine; CSF HVAFspinal fluid homovanillic acid; DLPFCFdorsolateral prefrontal cortex; PCPFphencylclidine; VTAFventral tegmental area; PFCFprefrontal cortex; AchFacetylcholine; NACFnucleus accumbens; SCZFschizophrenia; SPDFschizotypal personality disorder.…”
Section: The Effects Of Dopamine In Human and Animal Studiesmentioning
confidence: 99%
“…Aggressive and impulsive behaviors in rodents are modulated, in part, by DA activity at D1 and D2 receptors (Harrison et al, 1997;Vukhac et al, 2001). Dopamine-stimulated impulsive responses in rats are increased by central 5-HT depletion (Harrison et al, 1997).…”
Section: Da Dysfunction and Impulsive Behaviors In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5CSRTT assesses aspects of impulse control as well as attentional performance, speed of responding and motivation (Carli et al, 1983;Robbins, 2002). Harrison et al (1997a) showed that global 5-HT depletion increases premature responding on the 5CSRTT with concurrent decreases in omissions and latency to make a correct response. Intracerebral administration of the 5-HT neurotoxin, 5,7-dihydroxytryptamine (5,7-DHT) or specific lesions of serotonergic forebrain projections also increase impulsivity as well as impair attentional accuracy (Carli and Samanin, 1992;Jakala et al, 1992;Harrison et al, 1997a, b;Puumala and Sirviö, 1998;Winstanley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%